Racial classification in a CASE: reflections on black awareness, miscegenation and whiteness - Silva de Arruda, Jalusa; Agra Figueiredo, Otto Vinicius (Argumentum, 2020)
The article deals with racial classification in a community of socio-educational assistance (CASE), an institution with the task of carrying out the socio-educational measure of incarceration of adolescents and young authors of crime. It aims at ratifying the importance of racial classification for systematizing official data on the Brazilian socio-educational system, as well as reflecting on some of the implications that affect racial classification by third parties in institutions such as a CASE, especially from black awareness, miscegenation and whiteness approaches. It stems from some of the results of the doctoral research carried out in the Bahian socio-educational system, which adopted the technical assistance records as the main source of data collection. Keywords: Socio-educational system. Socio-educational measures of incarceration. Racial classification.